Contemporary issues in systems science and engineering - Zhou, MengChu; Li, Han-Xiong; Weijnen, M. P. C. (Hoboken, New Jersey : Wiley, 2015)
'This represents the most comprehensive systems engineering book, allowing systems engineers to evaluate increasingly complex problems and challenges through actual discrete events in order to reach the most effective solution. With world renowned systems engineers contributing, the book features 27 chapters, each on a different discrete event, with accompanying discussions and conclusions. The topics range from discrete event systems, distributed intelligent systems, grey systems, and enterprise information systems, to conflict resolution, robotics and intelligent sensing, systems biology, and system of systems approaches'--
Includes bibliographical references and index.
Keywords: Systems engineering